2008
DOI: 10.1007/s11998-008-9107-7
|View full text |Cite
|
Sign up to set email alerts
|

Water sorption and diffusional properties of a cured epoxy resin measured using alternating ionic liquids/aqueous electrolytes in electrochemical impedance spectroscopy

Abstract: The protective quality of a coating is often measured by how long it delays the arrival of water to the substrate. The transport of water in, redistribution within, and eventually through a coating to the substrate has long been investigated through electrochemical impedance spectroscopy (EIS). EIS measurements employing alternating nonaqueous (room temperature ionic liquids, RTIL) and aqueous electrolytes elucidated the behavior of water within the coating. Diffusion coefficients could be measured and the red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…It is frequently reported in the literature that the water diffusion coefficient in different epoxy systems is around 10 À8 to 10 À10 cm 2 /s. 4,24 The diffusion coefficient obtained in this study was found to be (5.1 ± 0.6) 9 10 À10 cm 2 /s, which is consistent with the reported data in literature. Barrier coatings based on polyurethane binders have a diffusion coefficient one order of magnitude less.…”
Section: Maximum Water Adsorbed and T G Changessupporting
confidence: 91%
See 1 more Smart Citation
“…It is frequently reported in the literature that the water diffusion coefficient in different epoxy systems is around 10 À8 to 10 À10 cm 2 /s. 4,24 The diffusion coefficient obtained in this study was found to be (5.1 ± 0.6) 9 10 À10 cm 2 /s, which is consistent with the reported data in literature. Barrier coatings based on polyurethane binders have a diffusion coefficient one order of magnitude less.…”
Section: Maximum Water Adsorbed and T G Changessupporting
confidence: 91%
“…For multi-layer coatings, penetration of water into the coating causes reduced adhesion between layers, interfacial cracking, and thereby can lead to corrosion on metallic substrates. 4,5 Moisture transport in polymer systems is related to polymer-water affinity, and to the environment. The polar nature of a typical coating polymer means that it will absorb moisture that may have a substantial effect on degradation chemistry, leaching and physical properties.…”
Section: Introductionmentioning
confidence: 99%
“…For exemplar calculations here, coating conductivity was assumed to constant and has a value of 10 −12 m as found in a high quality clearcoat epoxy coating [11]. Low resistivities produce a plateau in a Bode plot at lower frequencies, making the overall plot curved and thus obscuring the otherwise straight part due to the capacitance.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, these calculations demonstrate that needing to fit experimental results to an equivalent circuit containing a CPE, may only mean that the water content was changing during the experiment, and there may not be any other significant physical or chemical interpretation possible. Alternative means of performing EIS measurements without aqueous electrolytes, such as using room temperature ionic liquids [11] would eliminate the effects discussed here, since they are conducting liquids that do not seem to penetrate most films or cause any chemical change to the films or the substrate.…”
Section: Resultsmentioning
confidence: 99%
“…where R pc = polarization resistance for POEA coated Cu, R ps = polarization resistance for bare Cu substrate [13,[16][17][18]. The PE calculated from potentiodynamic polarization data is found to be ∼98%.…”
Section: Potentiodynamic Polarization Measurementsmentioning
confidence: 99%